Tracheal, bronchus, and lung cancer among older adults: thirty-year global burden trends, precision medicine breakthroughs, and lingering barriers - Hongquan Xing; Cong Wu; Weichang Yang; Shanshan Cai; Xinyi Zhang; Xiaoqun Ye (BMC Cancer)
Abstract Background Tracheal, bronchial, and lung (TBL) cancer presents significant health challenges for individuals aged 70 and older. However, comprehensive insights into the epidemiological patterns of and risk factors for TBL cancer in this population remain limited. This study aimed to analyze the global, regional, and national burdens and trends of TBL cancer patients aged ≥ 70 years from 1990–2021. Methods The incidence, mortality, and disability-adjusted life years (DALYs) for TBL cancer patients aged ≥ 70 years from 1990–2021 were obtained from the 2021 Global Burden of Disease study. Global trends were stratified age, sex, and sociodemographic index (SDI). Decomposition analysis identified the primary drivers of burden changes, and a global risk attribution analysis was conducted. The Bayesian Age‒Period‒Cohort (BAPC) model forecasted trends over the next 14 years. The analyses were performed with Joinpoint software and the R software. Results From 1990–2021, the ASIRs, ASMRs, and ASDRs of TBL cancer among patients ≥ 70 years increase significantly, mainly due to aging and population growth. In the precision medicine era (2015–2021), these indicators for both sexes and males have declined, but the burden among females has increased. The burden varies across regions, with the incidence of TBL cancer increasing more severely in middle-SDI regions, East Asia, and western sub-Saharan Africa, whereas high-SDI regions have shown a decline after peaking. Although the DALY proportion of smoking decreased, it was still the main cause of TBL cancer. However, the burden of environmental particulate pollution has increased. The BAPC model predicted that in the future, the ASIR, ASMR, and ASDR for males and both sexes would decrease, whereas these indicators would either remain stable or increase among females. Conclusions The burden of TBL cancer is increasing significantly among patients aged ≥ 70 years. Despite new hopes and approaches from precision medicine, environmental and behavioral factors still critically influence the TBL cancer burden. Future strategies could enhance subgroup-specific management and promote effective control of known risk factors.